Complex Binary Number System Algorithms and Circuits - Jamil, Tariq; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
This book is a compilation of the entire research work on the topic of Complex Binary Number System (CBNS) carried out by the author as the principal investigator and members of his research groups at various universities during the years 1992-2012. Pursuant to these efforts spanning several years, the realization of CBNS as a viable alternative to represent complex numbers in an 'all-in-one' binary number format has become possible and efforts are underway to build computer hardware based on this unique number system. It is hoped that this work will be of interest to anyone involved in computer arithmetic and digital logic design and kindle renewed enthusiasm among the engineers working in the areas of digital signal and image processing for developing newer and efficient algorithms and techniques incorporating CBNS.
Introduction -- Conversion Algorithms -- Arithmetic Algorithms -- Arithmetic Circuits Designs -- Complex Binary Associative Processor Design -- Conclusion and Further Research.
Keywords: Engineering; Computer science; Functions of complex variables; Algorithms; Systems engineering; Engineering; Circuits and Systems; Algorithms; Arithmetic and Logic Structures; Functions of a Complex Variable